PEMBUATAN DESINFEKTAN SEDERHANA MELALUI PEMANFATAAN BAHAN KARBOL DAN CAIRAN PEMUTIH PAKAIAN BAGI MASYARAKAT DI BALAI BARU KECAMATAN KURANJI KOTA PADANG - Fitri Rachmaini; Dian Ayu Juwita; Rahmad Abdillah (LPPM Universitas Andalas, 2023)
One of the efforts to break the chain of transmission of Covid-19 is to maintain cleanliness using an antiseptic to wash hands and body parts, as well as disinfectants that are sprayed or rubbed on various inanimate objects that may be exposed to the virus. However, there are still many people who are mistaken about using antiseptics and disinfectants, such as using antiseptics to clean items and the phenomenon of massive spraying of disinfectants in various places, even directly on humans. Apart from that, the lack of skills in making simple disinfectant fluids independently is also one of the triggering factors for the low level of concern in protecting the surrounding environment. The purpose of this activity is to educate the public about the correct use of antiseptics and disinfectants and to be able to utilize carbolic acid and liquid bleach to become simple disinfectants. This activity was carried out in Balai Baru Village, Kuranji District, Padang City. The method used in this activity is the presentation of the principles of the proper use of disinfectants and antiseptics as well as direct demonstrations of making simple disinfectants. The results of the activity are increased public understanding of the proper use of disinfectants and antiseptics as well as increased community skills in utilizing carbolic acid and clothing bleach into simple disinfectants. This activity is expected to be a reference in making simple disinfectants that are economical, environmentally friendly, and can be made by anyone. It is hoped that the chain of transmission of Covid-19 can be minimized.